The relationship between Strategic Knowledge Management and Organizational Innovation (Case Study: Bushehr's medical Sciences University and Health Care Center) - Parvaneh Rastgoo (International Review of Management and Marketing, 2017)
The present study was aimed to examine the relationship between knowledge management and organizational innovation in Bushehr's medical sciences university and health care services center (2016). Research method was practical in terms of objective; and in terms of data collection method, it was descriptive-survey. The statistical population of the present study consisted of 301 employees working in educational assistance, research and technology assistance, and student and culture assistance of Bushehr's medical sciences university and health care services center; from them, 170 individuals were selected as sample size, using a Morgan table and a stratified random sampling method. Data collection method was based on two questionnaires: 1) Mostafavi's standard strategic knowledge management questionnaire (2013), and 2) Chupany's organizational innovation questionnaire (2011). In the following, the reliability and validity of the questionnaire were approved; after the distribution and collection of the questionnaires, data examination and hypothesis testing were done using a Pearson Correlation method and a regression method, through SPSS software. Finally, the results of the present study show that there is a significant relationship between strategic knowledge management and its dimensions with organizational innovation (production innovation, process innovation, and official innovation) in the studied sample, i.e. Bushehr's medical sciences university and health care services center.